Temporal Flesh, Material Becomings. (March 2017) - simpkins, reese
Abstract : Drawing on contemporary trans* scholarship, I highlight an incorporeal, affective dimension of trans* embodiment, which I argue operates nonlinearly, enmeshing a past-present-future becoming. I show that the dynamic movement underlying both trans* and matter suggests their mutual imbrication—a mutual imbrication that trans*es materiality. Through the concept of autopoiesis, or the ability of systems to self-organise, I link trans*ed materiality at the micro level (cellular and quantum) to the social processes of trans* assemblages. Autopoiesis emerges as an affective realm, a dimension of trans*ed materiality and a process of trans* assemblages, all of which are integral in the production of space and time. As trans* bodies materialise, they create unique temporal embodiments that challenge universal frameworks of chronological time, highlight the nonlinear resonation of matter and enmesh past-present-future in open-ended becomings. The resulting ontogenetic, 'involutionary' processes of creative evolution produce unique temporalities that form the basis of new embodiments, new subjectivities, and new potentials for existence. As autopoietic processes produce new entities, the uniqueness of each becoming-trans* transforms the spatial and temporal context in which the becomings occur. Keeping in mind that becoming is never complete, I conclude that trans* temporalities are nonlinear, affective processes involved in the production of becoming-trans*. Trans* temporalities are, thus, entangled in an open-ended past-present-future.